A Passion for DNA : genes, genomes and society - Watson, James Dewey; Gratzer, Walter (Cold Spring Harbor Laboratory Press, 2000)
A principal architect and visionary of the new biology, a Nobel Prize-winner at 34 and best-selling author at 40 (The Double Helix), James D. Watson had the authority, flair, and courage to take an early and prominent role as commentator on the march of DNA science and its implications for society. In essays for publications large and small, and in lectures around the world, he delivered what were, in effect, dispatches from the front lines of the revolution. Outspoken and sparkling with ideas and opinions, a selection of them is collected for the first time in this volume. Their resonance with todayÂ’s headlines is striking.
Keywords: DNA; Genome; společnosti; genom; Genes; Societies; geny; genetika, lékařská genetika